Mutational and phenotypic spectra of KCNE1 deficiency in Jervell and Lange‐Nielsen Syndrome and Romano‐Ward Syndrome. Issue 2 (12th December 2018) - Faridi, Rabia; Tona, Risa; Brofferio, Alessandra; Hoa, Michael; Olszewski, Rafal; Schrauwen, Isabelle; Assir, Muhammad Z.K.; Bandesha, Akhtar A.; Khan, Asma A.; Rehman, Atteeq U.; Brewer, Carmen; Ahmed, Wasim; et al.
Abstract: KCNE1 encodes a regulatory subunit of the KCNQ1 potassium channel‐complex. Both KCNE1 and KCNQ1 are necessary for normal hearing and cardiac ventricular repolarization. Recessive variants in these genes are associated with Jervell and Lange‐Nielson syndrome (JLNS1 and JLNS2), a cardio‐auditory syndrome characterized by congenital profound sensorineural deafness and a prolonged QT interval that can cause ventricular arrhythmias and sudden cardiac death. Some normal‐hearing carriers of heterozygous missense variants of KCNE1 and KCNQ1 have prolonged QT intervals, a dominantly inherited phenotype designated Romano‐Ward syndrome (RWS), which is also associated with arrhythmias and elevated risk of sudden death. Coassembly of certain mutant KCNE1 monomers with wild‐type KCNQ1 subunits results in RWS by a dominant negative mechanism. This paper reviews variants of KCNE1 and their associated phenotypes, including biallelic truncating null variants of KCNE1 that have not been previously reported. We describe three homozygous nonsense mutations of KCNE1 segregating in families ascertained ostensibly for nonsyndromic deafness: c.50G>A (p.Trp17*), c.51G>A (p.Trp17*), and c.138C>A (p.Tyr46*). Some individuals carrying missense variants of KCNE1 have RWS. However, heterozygotes for loss‐of‐function variants of KCNE1 may have normal QT intervals while biallelic null alleles are associated with JLNS2, indicating a complex genotype‐phenotype spectrum for KCNE1 variants. Abstract : KCNE1 encodes a regulatory subunit of the KCNQ1 potassium channel‐complex. Both KCNE1 and KCNQ1 are necessary for normal hearing and cardiac ventricular repolarization. This paper reviews variants of KCNE1 and their associated phenotypes, including biallelic truncating null variants of KCNE1 that have not been previously reported. We describe three homozygous nonsense mutations of KCNE1 segregating in families ascertained ostensibly for nonsyndromic deafness: c.50G>A (p.Trp17*), c.51G>A (p.Trp17*), and c.138C>A (p.Tyr46*).